Swimmers' compliance with training prescription - Stewart, A. M.; Hopkins, W. G. (Medicine & Science in Sports & Exercise, 1997)
Ss in both conditions complied with completing distances and holding rest intervals to a very high degree. However, there was very little relationship between the prescribed intensity of the swimming and the intensity displayed by Ss (r = .30). (see also http://www.ncbi.nlm.nih.gov/entrez/query.fcgi?cmd=Retrieve&db=PubMed&list_uids=9346173&dopt=Abstract)